Antimicrobial and Adjuvant Potencies of Di-n-alkyl Substituted Diazalariat Ethers - Mohit B. Patel; Helena Spikes; Robert S. Bailey; Thomas Connell; Hannah Gill; Michael R. Gokel; Rebecca Harris; Joseph W. Meisel; Saeedeh Negin; Shanheng Andrew Yin; George W. Gokel (Antibiotics, 2023)
Lariat ethers are macrocyclic polyethers—crown ethers—to which sidearms are appended. 4,13-Diaza-18-crown-6 having twin alkyl chains at the nitrogens show biological activity. They exhibit antibiotic activity, but when co-administered at with an FDA-approved antibiotic, the latter’s potency is often strongly enhanced. Potency enhancements and resistance reversals have been documented in vitro for a range of Gram-negative and Gram-positive bacteria with a variety of antimicrobials. Strains of E. coli and Staphylococcus aureus having resistance to a range of drugs have been studied and the potency enhancements (checkerboards) are reported here. Drugs included in the present study are ampicillin, cefepime, chlortetracycline, ciprofloxacin, doxycycline, kanamycin, minocycline, norfloxacin, oxycycline, penicillin G, and tetracycline. Enhancements of norfloxacin potency against S. aureus 1199B of up to 128-fold were observed. The properties of these lariat ethers have been studied to determine solubility, their membrane penetration, cytotoxicity and mammalian cell survival, and their effect on bacterial efflux pumps. It is shown that in some cases, the lariat ethers have complex antimicrobials with considerable selectivity. Based on these observations, including 1:1 complexation between lariat ethers and antimicrobials and the cytotoxicity of the MeI salts showing a separation index of 32-fold, they hold significant potential for further development.